CREATING INDONESIAN YOUNG CONTENT CREATORS THROUGH CIJECT-BALE AS AN ENGLISH LEARNING INNOVATION - Eko Heriyanto; Ahmad Muhid (Universitas Ngudi Waluyo, 2021)
Since being introduced by the Minister of Education and Culture, the Kurikululm Merdeka dan Merdeka Belajar program has become a trend at the higher education level in Indonesia. On the other hand, the trend of the industrial world today is starting to touch the virtual world with several systems. The purpose of this study is to describe the implementation steps of Ciject-Bale as a creativity-based English learning method, the advantages of the Ciject-Bale method, and the effectiveness of this method in learning English. This research used descriptive qualitative and quantitative research methods with experimental research design. The results were the Ciject-Bale can be implemented through determining the theme and location, making the draft, doing a lot of practices, doing a live report, editing and uploading. Ciject-Bale has many advantages as an integrated English learning method and ICT. Through t-test analysis which showed that sig. (2-tailed) of all = 0.000 and the probability less than 0.05, Ciject-Bale was an effective method to be used in English learning. The conclusion was the learners will become young content creators in English by implementing this method and it needs more focus and high creativity.